Perancangan Animasi 3D Bertemakan Islami dengan Judul “Bersyukur” Menggunakan Metode Pose to Pose - Rashad Fathin Kurniawan (E-Jurnal Universitas Samudra, 2023)
Animated films are a form of film that a lot of people enjoy watching. A type of animated film is a 3D animated film. Therefore, this can be utilized by making 3D animated films combined with Islamic nuances, which can remind the small, but also important things for the daily life of Muslims. Like being grateful. Although being grateful is a very simple thing, people tend to not enjoy and feel less with what they have gotten. If all muslims are grateful about something, their blessings will be increased. This animation was created using the blender software. The making of the animation